PERANCANGAN DESAIN ANTARMUKA SMART E-COMMERCE PENJUALAN HASIL PERTANIAN (SiPeHtanI) BERBASIS WIREFRAMING - Pramadhana, Dian; Amalia, Dita Rizki; Ghozali, Ahmad Lubis (LPPM Institut Teknologi Bisnis Dan Bahasa Dian Cipta Cendikia, 2024)
Agriculture is a vital sector that supports the economy of many countries, especially in regions with fertile land and large agrarian communities. However, farmers often face challenges in marketing and selling their agricultural products. Limited access to broader markets and a lack of accurate information about market prices often make farmers reliant on intermediaries, who can suppress prices and reduce their income. Information and communication technology offers a solution through information systems that facilitate direct marketing. These systems enable farmers to sell their products directly to consumers or traders and access up-to-date market data, supporting better sales decisions and increasing efficiency and productivity. User interface (UI) design plays a crucial role in the success of these systems. An effective interface must be intuitive and easy to use for all users, including farmers, traders, and consumers with varying levels of technological understanding. Therefore, the design of the interface should consider ease of access and use for all user groups, including those less familiar with digital technology. This research aims to design a smart e-commerce interface for the sale of agricultural products using the Wireframing method. This method is expected to make the interface design process more systematic and efficient, as well as minimize the risk of failure.